2014
DOI: 10.2478/nuka-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in scalp hair of leukaemia patients

Abstract: Abstract. The aim of this study was to determine the concentration of Fe, Ni, Cu, Zn and Pb in scalp hair of leukaemia patients and healthy volunteers, using the optimised XRF method. Leukaemia hair samples were classifi ed corresponding to type, growth and age of the participants. The results showed that the studied trace elements (TEs) in both of leukaemia and control groups were positively skewed. In comparison with the control group, lower Fe, Cu, Zn and Pb and higher of Ni medians were found in all studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The comparison of essential trace (Cu, Fe and Zn) in referent subjects with reported literature data is presented in Table 7. The concentrations of zinc in scalp hair samples of referent subjects, found in present study, are comparable with Poland, Sudan, Italy, Pakistan and Syria studies [[78], [79], [80], [81], [82]], whilst higher than Ahmad et al, 2011 [83] and Pasha et al, 2010studies [84]. These findings are higher than Suliburska, 2011 study [85].…”
Section: Discussionsupporting
confidence: 86%
“…The comparison of essential trace (Cu, Fe and Zn) in referent subjects with reported literature data is presented in Table 7. The concentrations of zinc in scalp hair samples of referent subjects, found in present study, are comparable with Poland, Sudan, Italy, Pakistan and Syria studies [[78], [79], [80], [81], [82]], whilst higher than Ahmad et al, 2011 [83] and Pasha et al, 2010studies [84]. These findings are higher than Suliburska, 2011 study [85].…”
Section: Discussionsupporting
confidence: 86%
“…Chwiej et al 347,348 performed m-SRXRF measurements on animal models to elucidate the mechanisms involved in the pathogenesis and progress of epilepsy. Khuder et al 349 applied EDXRF to determine Br, Ca, Cl, Cu, Fe, K, Rb, S and Zn levels in the whole blood of leukemia patients and healthy volunteers. The study indicated different patterns of element distribution and mutual relationships in the whole blood of leukemia patients in comparison with controls.…”
Section: Clinicalmentioning
confidence: 99%